Vulnerability and Vulnerable Pregnancy. What is Bioethic’s Contribution? (Revista Iberoamericana de Bioética, 2017)
The article we present aims to discuss the appropriateness of terms such as vulnerability and vulnerable pregnancy in medical practice, as well as the attempt to recognize the specific contribution of bioethics in this discussion. Starting from a historical trajectory of the concept of vulnerability, the current confusing situation of the use of the category of vulnerable pregnancy is exposed. Finally, the relevance of the notion of vulnerability in the understanding of clinical practice from medical anthropology is acknowledged, and more rigorous interdisciplinary research is encouraged.
Keywords: vulnerability; bioethics; medicine; vulnerable pregnancy